Heart Poisoning: Medicine Unlike Any Other - Hawiger, Jacek (Ethics & medicine, 2019)
During the search for the circumstances of my father's death as a political prisoner in the Auschwitz concentration camp, I learned about one of the least known and most horrific aspects of the Holocaust. Phenol injections to the heart, that I term "heart poisoning," were an unusually gruesome act of killing, invented and executed by German doctors and their assistants. The rapid Nazification of German medicine and science led to the proliferation of such vicious method of extermination of approximately 20,000 Auschwitz prisoners, including children. Heart poisoning also terminated human sterilization experiments on imprisoned females and males and atrocious studies on twins and dwarfs. Most Nazi doctors who actively participated in this savage cycle of death in Auschwitz were recipients of doctoral degrees at wellknown German universities. At the end of World War II, some of them absconded, like physician-scientist Josef Mengele, while the others stood trials in Poland, the USSR, and West Germany. The Nuremberg Code of medical ethics was subsequently enacted. As our collective memory fades and 66% millennials who were born in the United States after 1983 are unfamiliar with Auschwitz, this darkest chapter of a medicine unlike any other should inform the bioethical underpinnings of contemporary medical and nursing education and practice.